The Synthesis of Conical Carbon. Issue 3 (25th January 2021) - Zhang, Qianyan; Xie, Xiao‐Ming; Wei, Shi‐Yao; Zhu, Zheng‐Zhong; Zheng, Lan‐Sun; Xie, Su‐Yuan
Abstract: Conical carbon, specifically multi‐walled carbon nanocones (CNCs) and single‐walled carboncones, is a new class of sp 2 ‐hybridized carbon allotrope, in addition to fullerene, carbon nanotubes (CNTs), and graphene. Characterized by a conical and delocalized aromatic configuration, the conical carbon structure is considered the intermediate structure between planar graphene and open‐cage fullerene. CNCs can be stiffer than CNTs and exhibit intriguing physical and chemical properties owing to their unique hollow conical structure, which make these materials promising for application as field emission sources and scanning probes. The research on conical carbon structures is in its nascent stage, mainly because of the limitations in the synthesis and purification of conical carbons. This review summarizes the significant progress in the synthesis of CNCs and carboncones. Particularly, the synthetic methods, which can be divided into traditional physical‐chemical synthesis methods for multi‐walled CNCs and emerging bottom‐up organic synthesis methods for single‐walled carboncones, are comprehensively discussed. In addition, the advantages and disadvantages of the various synthetic methods as well as the possible formation and growth mechanisms of CNCs and carboncones are discussed. Finally, some outlooks on the potential solutions to the synthesis of single‐walled carboncones with uniform apex angles are presented. Abstract : The cone angles of carbon nanocones (CNCs) or carboncones are determined by the number of pentagons (1–5) in the cone tip. CNCs are multi‐walled conical carbon structures produced by traditional physical‐chemical methods, while carboncones are single‐walled conical carbon structures prepared by the emerging bottom‐up organic approaches. The advantage of organic approaches is the fabrication of conical carbons with well‐defined single‐walled structures.